Το λογιστικό - κοστολογικό πληροφοριακό σύστημα διοίκησης (M.I.S) με εφαρμογή στον τραπεζικό τομέα : - Αρσένος, Παναγιώτης Ι., 1961- (2006)
Επταμελής επιτροπή: Βασίλειος Αγγελής, Νικήτας Νιάρχος, Δημήτριος Βασιλείου, Διονύσιος Χιόνης, Ελένη Ρογδάκη, Νικόλαος Ηρειώτης, Μιχαήλ Μπεκιάρης